Tooth Profile Modification Method and Life Prediction Analysis of Cup Type Harmonic Reducers - Mei Jie; Zhang Tong; Guo Zheng; Chen Dingfang; Wu Junfeng; Zhang Huiming; Hu Qunfei (Jixie chuandong)
The theory of the radial deformation generated by the assembly of the flexwheel and the wave generator of the cup harmonic reducer is inconsistent with the practice, and the tooth meshing interferes between the flexwheel and the rigid wheel. Based on the deformation of the flexwheel assembly, a method for modifying the tooth profile of the flexwheel was put forward, and the appropriate modification amount was determined through the finite element assembly simulation. After the modification, the flexwheel was assembled and run through the finite element analysis. Finally, based on the Miner linear fatigue theory, the Fe-safe software was used to predict the life of flexwheels. The results show that the maximum stress during the assembly of the flexwheel is reduced from 962.2 MPa to 532.7 MPa, the stress during load operation is 609.9 MPa, the tooth stress is greatly improved, the meshing interference is solved, and the life cycle of the flexwheel is 4.28×106 times.